OUTSOURCING AS A MODERN TOOL FOR IMPROVING BUSINESS EFFICIENCY - Samenova Ainura Mukhtarovna (Arts Academy)
The article explores the role of outsourcing in the modern business environment and its importance for improving the efficiency of business processes. The main aspects of outsourcing are considered, including its definition, the main advantages and risks, such issues of the main advantages of outsourcing as cost reduction, increased flexibility and access to expertise and resources that can significantly improve the operational efficiency and competitiveness of the company are touched upon. In conclusion, the author comes to the conclusion that outsourcing is an important and effective tool for improving business efficiency but requires careful planning and management to avoid potential problems.